The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1093/cid/cis357
|View full text |Cite
|
Sign up to set email alerts
|

Relapse Versus Reinfection: Recurrent Clostridium difficile Infection Following Treatment With Fidaxomicin or Vancomycin

Abstract: Our study sought to compare the strain types of Clostridium difficile causing initial and recurrent episodes of C. difficile infection (CDI) in adult patients with a first episode of CDI or 1 prior episode of CDI within the previous 90 days. Strains originated from patients who had been entered into two phase 3 randomized clinical trials of fidaxomicin versus vancomycin. Isolates of C. difficile from the initial and recurrent episodes within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
86
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(89 citation statements)
references
References 13 publications
0
86
1
2
Order By: Relevance
“…This finding is consistent with a recent point-prevalence investigation of C. difficile environmental contamination in a hos- MLVA is an objective, highly discriminatory molecular genotyping tool that can be used to define relapse versus reinfection in recurrent CDI cases. We report rates of relapse in our study that were lower than the rates in recent reports that used PCR-ribotyping, multilocus sequence typing (MLST), and REA to classify recurrent CDI (7,8,13). These methods may overestimate relapse and underestimate reinfection rates because they are less discriminatory than MLVA (14).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…This finding is consistent with a recent point-prevalence investigation of C. difficile environmental contamination in a hos- MLVA is an objective, highly discriminatory molecular genotyping tool that can be used to define relapse versus reinfection in recurrent CDI cases. We report rates of relapse in our study that were lower than the rates in recent reports that used PCR-ribotyping, multilocus sequence typing (MLST), and REA to classify recurrent CDI (7,8,13). These methods may overestimate relapse and underestimate reinfection rates because they are less discriminatory than MLVA (14).…”
Section: Discussionmentioning
confidence: 54%
“…Two very recent studies have described increased recurrence rates and a trend toward a higher incidence of relapse among patients infected with BI strains as defined by REA typing (8,26). These data could have major implications for treatment and development of new therapeutics that specifically target infection with BI/NAP1/027 strains.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Patients usually present with fever, abdominal pain, diarrhea, loss of appetite and fatigue [20]. Clostridium difficile-associated diarrhea seems to be on the increase and is implicated in 20-30% of all antibiotic associated diarrheal cases [21]. Fatal cases caused by toxin A and B producing Clostridium difficile strains, have been reported in countries such as, Canada, United States and Europe [7,11,14,22].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, there are no formal recommendations to alter treatment based solely on the strain causing the infection. Some strain types may correlate with an increased risk of recurrent disease (23). In the initial fidaxomicin treatment study, the data showed that the risk of relapse may vary depending upon the C. difficile strain type (24).…”
Section: Discussionmentioning
confidence: 99%